Konstruksi Identitas Budaya melalui Perkebunan: Studi Literatur terhadap Komunitas Aceh, Melayu, dan Tionghoa di Indonesia - Marzuti Isra; Nayla Rashifa; Ersandi Roihan Putra; Reza Syahputra; Rifadeo Rahmad Siregar; Fachry Pahlevi Siregar (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This literature study examines the construction of cultural identity through socio-economic practices in plantation ecosystems among the Acehnese, Malay, and Chinese communities in Indonesia. Using a systematic literature review of 42 selected sources (1990-2023), the research reveals that plantations function as sites of identity negotiation—dynamic arenas of cultural adaptation and resistance. In Aceh, the integration of Islamic values (zakat [alms] from plantations, meunasah education) and local wisdom (peusijuek rituals) mediates post-conflict reconciliation and identity transformation from "combatants" to "farmers" (Muchlis et al., 2023; Aulia et al., 2024). For the Malay community, the customary-territorial concept of bela kampung (communal defense) underpins resistance to authority fragmentation through gotong royong (mutual cooperation) and communal land allocation (Yunanda et al., 2024; Nasution et al., 2024). Meanwhile, the Chinese community develops invisibility strategies (e.g., land acquisition via family foundations, citizenship aliases) to convert legal marginalization into clan-based social capital (Irawan, 2016; Thung, 2018). Key findings highlight divergent identity sources: religiosity (Aceh), customary-territoriality (Malay), and clan social capital (Chinese). The study recommends integrating local wisdom into inclusive plantation policies and employing ethnographic approaches to examine identity intersectionality complexity.